Disability, market and non-market work in the perspective of the policy of life and opening windows of opportunities - Giermanowska, Ewa (Research on social problems in (pre-)pandemic reality, 2023)
In modern societies, professional work of people with disabilities and professional activation programs have become the norm. Their right to work on an equal basis with others and the promotion of equal opportunities in the field of training and employment set the directions of action in international and national politics [[UN Convention on the Rights of Persons with Disabilities 2006]. The failures of numerous professional activation programs for people with disabilities raise the question of the boundaries of activation and limitations of the process of normalizing market policies and work ideologies. In this context, "refusal to work" can become a sanctioned choice. Changing lifestyles and work styles strengthen alternative choices and the acceptance process for other forms of work, which may include, among others, caring work, social work, disease management, rehabilitation. Referring to Giddens' concept of the politics of emancipation and the politics of life in late modern societies, it is worth considering the forms of work alternative to market labor and the choices of lifestyles. The current political activities are focused primarily on increasing the professional activity of people with disabilities. However, it cannot be ruled out that in the process of creating politics and political games [Kingdon 1995] new solutions will emerge and "windows of opportunity" will be created for the recognition of alternative forms of work. The communities of people with disabilities will play a key role in introducing new solutions and opening "windows of opportunities".